Near-zero energy dissipation multilayer ceramic capacitors via inhomogeneous polarization design - Liu, Jinnan; Zhao, Weichen; Ren, Jiajia; Liu, Wenyuan; Li, Da; Wang, Zhentao; Liu, Yang; Liu, Wenfeng; Zhou, Tao; Xu, Diming; Chen, Guohua; Tan, Kar Ban; et al. (John Wiley and Sons, 2025)
Multilayer ceramic capacitors (MLCCs) demonstrate considerable potential for advance pulsed power systems, owing to their high-power density and fast charge/discharge capabilities. In light of the increasing demand for energy conservation, minimizing energy dissipation in storage capacitors while maintaining high recoverable energy densities is essential for their practical application. In this study, building upon the morphotropic phase boundary (MPB) between Bi0.5Na0.5TiO3 (BNT) and NaNbO3, heterogeneous cations (Ba2+, Zn2+, and Nb5+) are further doped using an inhomogeneous polarization design to enhance the random field. This strategy leads to the formation of a disordered polarized structure with nanoscale multiphase characteristics. The results indicate that the BNT-based MLCC achieves a high recoverable energy density (Wrec ≈ 9.1 J·cm−3) and an exceptionally high energy storage efficiency (η ≈ 97.5%) under 620 kV·cm−1. In addition, the MLCC exhibits excellent stability across a wide range of temperatures and frequencies, coupled with exceptional charge/discharge performance. This study offers a practical approach for the future development of BNT-based MLCCs with near-zero energy dissipation.